WAO consensus on DEfinition of Food Allergy SEverity (DEFASE) - Arasi, S; Nurmatov, U; Dunn-Galvin, A; Roberts, G; Turner, PJ; Shinder, SB; Gupta, R; Eigenmann, P; Nowak-Wegrzyn, A; Ansotegui, IJ; Rivas, MF; Petrou, S; et al. (Elsevier, 2023)
Background: While several scoring systems for the severity of anaphylactic reactions have been developed, there is a lack of consensus on definition and categorisation of severity of food allergy disease as a whole.